2021
DOI: 10.2147/nss.s313373
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Quarantine on Sleep Quality and Psychological Distress During the COVID-19 Pandemic

Abstract: Purpose: We investigated the impact of isolation on sleep quality and psychological distress during the COVID-19 pandemic in Saudi Arabia. Methods: An online survey was conducted on 353 (88 isolated and 265 not isolated) individuals from May to June 2020. Subjective sleep quality was determined using the Pittsburgh sleep quality index (PSQI), and psychological distress measured using the Kessler psychological distress scale (K10). Results: The mean age of the isolated group was 28.6 years versus 27.5 years for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 50 publications
0
23
0
1
Order By: Relevance
“…Furthermore, sleep of the same duration can be more or less restorative depending upon mood state and level of stress. The adverse effects of "lockdown" on mood and sleep were emphasized in numerous recent publications [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. It an not be excluded that stressful situations caused by "lockdown" resulted in a longer but less restorative sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sleep of the same duration can be more or less restorative depending upon mood state and level of stress. The adverse effects of "lockdown" on mood and sleep were emphasized in numerous recent publications [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. It an not be excluded that stressful situations caused by "lockdown" resulted in a longer but less restorative sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Many sleep scientists used sleep quality or similar constructs to document changes in sleep during the COVID-19 quarantines. Many studies across numerous countries reported a worsening of sleep quality, increasing sleep problems, or increasing problems with insomnia during quarantine conditions ( Blume et al, 2020 ; Peretti-Watel et al, 2020 ; Pinto et al, 2020 ; Voitsidis et al, 2020 ; AlRasheed et al, 2021 ; Cellini et al, 2021 ; Conte et al, 2021 ; Hisler and Twenge, 2021 ; Hyun et al, 2021 ; Marelli et al, 2021 ; Martínez-de-Quel et al, 2021 ; Robillard et al, 2021 ). However, some studies found that sleep quality did not worsen across all participants ( Benham, 2020 ; Gao and Scullin, 2020 ; Kocevska et al, 2020 ; Tahara et al, 2021 ).…”
Section: Social Isolation and Sleep During Covid-19mentioning
confidence: 99%
“… 4 However, these measures combined with the continuous spread of the virus have profoundly changed people’s lifestyles and negatively affected their mental health and well-being. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%